Directional electromagnetic steel sheet
By controlling grain size and applying laser irradiation, the grain-oriented electrical steel sheet addresses the 200Hz component of magnetostriction, achieving low iron loss and noise reduction in transformers.
Patent Information
- Application Number
- JP2024512993
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-09-22
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2043-09-22
AI Technical Summary
Existing grain-oriented electrical steel sheets do not adequately address the reduction of the 200Hz component of the magnetostrictive waveform, which is correlated with transformer noise, while maintaining low core loss and noise levels.
Control the grain size by adjusting the distance between grain boundaries in the rolling direction and applying laser irradiation to reduce magnetostriction without impairing core loss, using a specific chemical composition and structural modifications.
Achieves a grain-oriented electrical steel sheet with low iron loss and noise, characterized by controlled grain boundaries and laser-induced magnetic domain patterns, effectively reducing transformer noise.
Smart Images

Figure 0007602187000003 
Figure 0007602187000004 
Figure 0007602187000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a grain-oriented electrical steel sheet. This application claims priority based on Japanese Patent Application No. 2022-151341, filed on September 22, 2022, the contents of which are incorporated herein by reference. [Background technology]
[0002] In recent years, there has been an increasing demand for reduced noise and vibration in electromagnetic equipment such as transformers, and the grain-oriented electrical steel sheets used in the iron cores of transformers are now required to be materials that are suitable for low noise and vibration as well as low core loss. One of the causes of noise and vibration in transformers is said to be magnetostriction in grain-oriented electrical steel sheets. Magnetostriction here refers to vibrations observed in the rolling direction of grain-oriented electrical steel sheets, which are caused by slight changes in the external shape of the grain-oriented electrical steel sheet due to changes in the strength of magnetization when the grain-oriented electrical steel sheet is excited with an alternating current. The magnitude of this magnetostriction is 10 -6 Although it is on the order of a very small magnitude, the magnetostriction generates vibrations in the iron core, which are transmitted to external structures such as the transformer tank and result in noise.
[0003] Magnetostriction properties change depending on various factors such as the structure and condition of the grain-oriented electrical steel sheet, specifically the degree of crystal orientation integration, the tension applied to the steel sheet by the insulating coating, the strain inherent in the steel, etc. When the magnetostriction properties change, the noise level also changes, and in some cases it is possible to reduce noise.
[0004] For example, Patent Document 1 discloses a grain-oriented electrical steel sheet that can reduce noise from electrical components when used as a material for the components, the grain-oriented electrical steel sheet having an average grain length in the rolling direction DLmax of 12 mm or more, a coating tension of 1 MPa or less, and a sheet thickness of 0.35 mm or less, in which the grain length in the rolling direction is divided into four equal regions, and in the two outer regions, the grain boundary vicinity region is within a distance of 2 mm from the grain boundaries in the inner direction of the grains, where β is the absolute value of the crystal orientation recession angle, and (area of the grain boundary vicinity region where β is 4.0° or less) / (total area of the grain boundary vicinity region) ≧ 0.50.
[0005] Patent Document 2 describes a grain-oriented electrical steel sheet having excellent magnetostriction properties, which contains 3.0-7.0 mass% Si, 0.04-0.15 mass% Mn, 0.01-0.10 mass% Sb, and 0.01-0.20 mass% Sn, with the balance being Fe and unavoidable impurities, and is coated with a tension-applying insulating coating such that the total tensile stress, including that of a forsterite coating, is 10 MPa or more, and the steel sheet has a Goss orientation {110} <001> The average misorientation angle δ of the crystal orientation with the rolling direction as the rotation axis in the grains is 6° or less, and the magnetostriction λ when a compressive stress of 3.92 MPa is applied in the rolling direction and magnetized at 50 Hz and 1.7 T is p-p is 1.7 × 10 -6 The following grain-oriented electrical steel sheet is disclosed.
[0006] However, the above techniques do not sufficiently improve the iron loss characteristics (reduction of iron loss). It is known that irradiating the surface of grain-oriented electrical steel sheet with a laser or the like to control the magnetic domains is an effective way to reduce iron loss, but the methods of Patent Documents 1 and 2 cannot be applied to laser-irradiated materials.
[0007] As a technology for reducing iron loss and magnetostriction by laser beam irradiation, Patent Document 3 describes a technology for reducing iron loss and magnetostriction by irradiating a laser beam, in which the magnetic flux density B8 of a steel sheet generated by a magnetizing force of 800 A / m is 1.92 T or more, and the rolling direction and the easy axis of magnetization (100) are aligned in the same direction. <001> The method for producing a grain-oriented electrical steel sheet is disclosed, in which a grain-oriented electrical steel sheet having an Rs of 30% to 100%, where the component of the angle deviation in the sheet thickness direction is the β angle, and the proportion of the total area of crystal grains that simultaneously include regions in which the absolute value of the β angle is 0.5° or less and regions in which the absolute value of the β angle is 2° to 6°, is taken as the β angle, and the surface of the grain-oriented electrical steel sheet is periodically irradiated with a laser beam generated by a fiber laser having a fiber core diameter of 5 μm to 400 μm substantially perpendicularly to the rolling direction of the grain-oriented electrical steel sheet, and the width in the rolling direction of the surface irradiation marks of the laser beam or the width in the rolling direction of the closure magnetic domains formed in the laser irradiated portions is 10 μm to 200 μm, thereby reducing iron loss compared to before the laser beam irradiation. Patent Document 3 shows that the above method can provide a grain-oriented electrical steel sheet with extremely low iron loss and magnetostriction, particularly in grain-oriented electrical steel sheets with high magnetic flux density.
[0008] However, according to the study by the present inventors, it was found that reducing the 200 Hz component of the magnetostrictive waveform is effective in reducing the noise of the transformer. In the technology of Patent Document 3, the 200 Hz component of the magnetostrictive waveform was not studied, and the characteristics were not sufficient in some cases.
[0009] Patent Document 4 discloses a new and improved method for producing grain-oriented electrical steel sheet, which is capable of producing grain-oriented electrical steel sheet with lower core loss when a rapid heating rate faster than conventional is performed in primary recrystallization annealing, and a grain-oriented electrical steel sheet produced by said method. Patent Document 4 indicates that the above technology can reduce noise while improving the magnetic properties of the transformer.
[0010] However, the 200 Hz component of the magnetostrictive waveform is not considered in Patent Document 4 either. Furthermore, Patent Document 4 states that it is anticipated that magnetic domain control processing will increase noise in the transformer. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent No. 6606991 [Patent Document 2] Japanese Patent No. 5896112 [Patent Document 3] Japanese Patent No. 4616623 [Patent Document 4] International Publication No. 2019 / 181952 Summary of the Invention [Problem to be solved by the invention]
[0012] As described above, in the past, there had been no disclosure of grain-oriented electrical steel sheets that were based on the implementation of magnetic domain control by laser irradiation to reduce iron loss, and that reduced the 200 Hz component of the magnetostriction waveform that correlates with transformer noise. Therefore, an object of the present invention is to provide a grain-oriented electrical steel sheet that is suitable for application to transformers and the like and has low iron loss and low noise. [Means for solving the problem]
[0013] The present inventors have investigated the reduction of transformer noise, and have found that the transformer noise is strongly correlated with the 200 Hz component of the magnetostrictive waveform, and that the transformer noise can be reduced by reducing the 200 Hz component of the magnetostrictive waveform.
[0014] In addition, when a laser is irradiated onto the surface of a grain-oriented electrical steel sheet in order to reduce iron loss, magnetostriction generally increases. In other words, there is a trade-off between reducing iron loss and reducing magnetostriction. Therefore, in the past, when reducing magnetostriction, it was necessary to select conditions for reducing magnetostriction by sacrificing the effect of reducing iron loss to some extent by adjusting the irradiation conditions such as the laser intensity. However, it is difficult to simultaneously further reduce the core loss and magnetostriction by simply adjusting the conditions of the laser irradiation. Therefore, the present inventors have investigated a method for reducing magnetostriction (particularly the 200 Hz component of the magnetostrictive waveform) without compromising iron loss by controlling the structure, etc. of grain-oriented electrical steel sheet. As a result, they found that magnetostriction can be reduced without impairing iron loss by controlling the grain size (especially the distance between grain boundaries in the rolling direction). They also found that changing the curvature of the steel sheet by taking special measures during coiling is effective for controlling the grain size.
[0015] The present invention has been made in view of the above findings. [1] A grain-oriented electrical steel sheet according to one embodiment of the present invention comprises a base steel sheet, a forsterite film formed on a surface of the base steel sheet, and an insulating film formed on the surface of the forsterite film, the base steel sheet having a chemical composition, in mass%, containing Si: 0.80 to 7.00%, the area ratio of crystal grains on the surface of the base steel sheet, the distance between grain boundaries of crystal grains in the rolling direction being 3.0 mm or more and 13.0 mm or less, is 70% or more, B8, which is a magnetic flux density generated by a magnetizing force of 800 A / m, is 1.88 T or more, and W17 / 50, which is an iron loss when a frequency is 50 Hz and a maximum magnetic flux density is 1.7 T, is 13.1 x t, in W / kg, where t is a thickness of the base steel sheet in mm. 2 -4.3×t+1.2 or less, and LvA200Hz, which is the 200Hz component of the magnetostrictive waveform, is 60 to 78dBA. A plurality of linear strains extending in a direction intersecting the rolling direction are formed on the surface of the base steel plate, and the intervals between the plurality of linear strains in the rolling direction are 3 to 10 mm. Grain-oriented electrical steel sheet. [ 2 ] [1] The grain-oriented electrical steel sheet described may be such that, in the base steel sheet, the area ratio of the rectangular closure domains observed on the surface is 10% or less, and the width of the stripe-shaped main domains is 1.2 mm or less. [ 3 In the grain-oriented electrical steel sheet according to [1] or [2], when the magnetic flux density is 1.92 T or more and the sheet thickness is 0.18 to 0.23 mm, the W17 / 50 may be 0.74 W / kg or less. 。 Effect of the Invention
[0016] According to the above-described aspect of the present invention, it is possible to provide a grain-oriented electrical steel sheet having low iron loss and low noise (excellent iron loss characteristics and noise characteristics). [Brief description of the drawings]
[0017] [Figure 1] This is an example of the observed magnetic domain pattern. [Diagram 2] FIG. 2 is a diagram illustrating a closure domain (lancet). [Diagram 3] 1A to 1C are diagrams showing examples of the arrangement of spacers placed between steel sheets in a winding process. [Figure 4] FIG. 2 is a diagram showing an example of a mode in which an annealing separator is applied in a coiling process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] A grain-oriented electrical steel sheet according to one embodiment of the present invention (grain-oriented electrical steel sheet according to this embodiment) comprises a base steel sheet, a forsterite film formed on the surface of the base steel sheet, and an insulating film formed on the surface of the forsterite film. Furthermore, in the grain-oriented electrical steel sheet according to the present embodiment, the chemical composition of the base steel sheet contains, in mass%, 0.80 to 7.00% Si, the area ratio of crystal grains on the surface of the base steel sheet in which the distance between the grain boundaries of crystal grains in the rolling direction is 3.0 mm or more and 13.0 mm or less is 70% or more, B8, which is the magnetic flux density generated by a magnetizing force of 800 A / m, is 1.88 T or more, and W17 / 50, which is the iron loss when the frequency is 50 Hz and the maximum magnetic flux density is 1.7 T, is 13.1×t in W / kg, where t is the sheet thickness in mm. 2 -4.3×t+1.2 or less, and LvA200Hz, which is the 200Hz component of the magnetostrictive waveform, is 60 to 78dBA. Each of these will be explained below.
[0019] <Base material steel plate> (chemical composition) Si: 0.80-7.00% Silicon (Si) is an element that increases the electrical resistance of grain-oriented electrical steel sheets and improves their core loss characteristics. If the Si content is less than 0.80%, a sufficient eddy current loss reduction effect cannot be obtained. Therefore, the Si content is set to 0.80% or more. The Si content is preferably 1.00% or more, and more preferably 1.20% or more. On the other hand, if the Si content exceeds 7.00%, the steel sheet becomes embrittled and may break during rolling. Also, the workability of the grain-oriented electrical steel sheet decreases. For this reason, the Si content is set to 7.00% or less. The Si content is preferably 6.80% or less, more preferably 6.70% or less, and even more preferably 4.00% or less.
[0020] The base steel sheet included in the grain-oriented electrical steel sheet according to this embodiment has a chemical composition containing, in mass %, 0.80 to 7.00% Si, and there are no particular limitations on the contents of other elements. However, depending on the properties required for the grain-oriented electrical steel sheet, the components (elements) constituting the chemical composition may contain the following elements in addition to Si, within the ranges shown below. In this embodiment, % relating to the content of each element is % by mass, unless otherwise specified.
[0021] C: 0.070% or less C (carbon) is an element effective for controlling the structure of the steel sheet in the process up to the completion of the decarburization annealing process in the manufacturing process. However, if the C content exceeds 0.070%, the magnetic properties of the finished grain-oriented electrical steel sheet deteriorate. Therefore, in the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment, the C content is preferably 0.070% or less. The C content is more preferably 0.050% or less, and further preferably 0.020% or less. The lower the C content, the more preferable it is, but even if the C content is reduced to less than 0.0001%, the effect of controlling the structure is saturated and the manufacturing cost is simply increased. Therefore, the C content may be 0.0001% or more.
[0022] Mn: 0.01 to 0.50% Mn (manganese) is an element that combines with S to form MnS during the manufacturing process. These precipitates function as inhibitors (suppressants of normal grain growth) and cause secondary recrystallization in steel. Mn is also an element that improves the hot workability of steel. If the Mn content is less than 0.01%, the above-mentioned effects cannot be fully obtained. Therefore, the Mn content is preferably 0.01% or more. The Mn content is more preferably 0.02% or more. On the other hand, if the Mn content exceeds 0.50%, secondary recrystallization does not occur and the magnetic properties of the steel deteriorate. Therefore, in the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment, the Mn content is preferably 0.50% or less. The Mn content is more preferably 0.20% or less, and further preferably 0.10% or less.
[0023] N: 0.0100% or less N (nitrogen) is an element that combines with Al in the manufacturing process to form AlN, which functions as an inhibitor. If the N content exceeds 0.0100%, the inhibitor remains in the grain-oriented electrical steel sheet in excess, resulting in reduced magnetic properties. Therefore, in the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment, the N content is preferably 0.0100% or less. The N content is more preferably 0.0080% or less. On the other hand, the lower limit of the N content is not particularly specified, but reducing the N content to less than 0.0010% would only increase the manufacturing cost, and therefore the N content may be set to 0.0010% or more.
[0024] Sol.Al: 0.030% or less Sol.Al (acid-soluble aluminum) is an element that combines with N to form AlN, which functions as an inhibitor, during the manufacturing process of the grain-oriented electrical steel sheet. However, if the sol.Al content of the base steel sheet exceeds 0.030%, the inhibitor remains in the base steel sheet in excess, and the magnetic properties are reduced. Therefore, in the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment, the sol.Al content is preferably 0.030% or less. The sol.Al content is more preferably 0.020% or less, and further preferably 0.015% or less. The lower limit of the sol.Al content is not particularly specified, but even if it is reduced to less than 0.0001%, the manufacturing cost will only increase. Therefore, the sol.Al content may be 0.0001% or more.
[0025] S: 0.010% or less S (sulfur) is an element that combines with Mn in the manufacturing process to form MnS, which functions as an inhibitor. However, if the S content exceeds 0.010%, the magnetic properties are reduced due to the remaining inhibitor. Therefore, in the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment, the S content is preferably 0.010% or less. The S content in the grain-oriented electrical steel sheet is preferably as low as possible. For example, it is less than 0.001%. However, even if the S content in the grain-oriented electrical steel sheet is reduced to less than 0.0001%, the manufacturing cost will only increase. Therefore, the S content in the grain-oriented electrical steel sheet may be 0.0001% or more.
[0026] Remainder: Fe and impurities The chemical composition of the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment may contain, for example, the above-mentioned elements, with the balance being Fe and impurities. However, for the purpose of improving magnetic properties, etc., P, Cr, Sn, Cu, Se, Sb, and Mo may be further contained in the ranges shown below (since they may not be contained, the lower limit is 0%). Furthermore, even if other elements than these, such as W, Nb, Ti, Ni, Bi, Co, and V are contained in a total of 1.0% or less, this does not impair the effects of the grain-oriented electrical steel sheet according to this embodiment. Here, impurities refer to elements that are mixed in from raw materials such as ore or scrap, or from the manufacturing environment, during industrial production of the base steel sheet, and are permissible to be contained in amounts that do not adversely affect the function of the grain-oriented electrical steel sheet according to this embodiment.
[0027] P: 0~0.030% P (phosphorus) is an element that reduces workability in rolling. By setting the P content to 0.030% or less, it is possible to prevent the rolling workability from being excessively reduced, and to prevent breakage during production. From this viewpoint, the P content is preferably set to 0.030% or less. The P content is more preferably set to 0.020% or less, and further preferably set to 0.010% or less. There is no lower limit for the P content, and the P content may be 0%, but in practical steel sheets, the substantial lower limit for the P content is 0.0001%. P is also an element that has the effect of improving the texture and magnetic properties. To obtain this effect, the P content may be 0.001% or more, or 0.005% or more.
[0028] Cr: 0~0.50% Cr (chromium) is an element that contributes to increasing the Goss orientation occupancy rate in the secondary recrystallized structure and improves magnetic properties. In order to obtain the above effect, the Cr content is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.10% or more. On the other hand, if the Cr content exceeds 0.50%, Cr oxides are formed and the magnetic properties deteriorate. Therefore, the Cr content is preferably 0.50% or less. The Cr content is more preferably 0.30% or less, and further preferably 0.15% or less.
[0029] Sn: 0 to 0.50% Sn (tin) is an element that contributes to improving magnetic properties through controlling the primary recrystallization structure. In order to obtain the effect of improving magnetic properties, the Sn content is preferably 0.01% or more. The Sn content is more preferably 0.02% or more, and further preferably 0.03% or more. On the other hand, if the Sn content exceeds 0.50%, the secondary recrystallization becomes unstable and the magnetic properties deteriorate. Therefore, the Sn content is preferably 0.50% or less. The Sn content is more preferably 0.30% or less, and further preferably 0.10% or less.
[0030] Cu: 0-0.50% Cu (copper) is an element that contributes to an increase in the Goss orientation occupancy rate in the secondary recrystallized structure. Cu is an optional element in the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment. Therefore, the lower limit of the Cu content is 0%, but in order to obtain the above effect, the Cu content is preferably 0.01% or more. The Cu content is more preferably 0.02% or more, and further preferably 0.03% or more. On the other hand, if the Cu content exceeds 0.50%, the steel sheet becomes embrittled during hot rolling. Therefore, in the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment, the Cu content is preferably 0.50% or less. The Cu content is more preferably 0.30% or less, and further preferably 0.10% or less.
[0031] Se: 0 to 0.020% Se (selenium) is an element that has a magnetic property improving effect. Therefore, it may be contained. When Se is contained, the content is preferably 0.001% or more in order to exhibit the magnetic property improving effect well. The Se content is more preferably 0.003% or more, and further preferably 0.006% or more. On the other hand, if the Se content exceeds 0.020%, the adhesion of the forsterite film deteriorates. Therefore, the Se content is preferably 0.020% or less. The Se content is more preferably 0.015% or less, and further preferably 0.010% or less.
[0032] Sb: 0 to 0.50% Sb (antimony) is an element that has a magnetic property improving effect. Therefore, it may be contained. When Sb is contained, the content is preferably 0.005% or more in order to exhibit the magnetic property improving effect well. The Sb content is more preferably 0.01% or more, and further preferably 0.02% or more. On the other hand, if the Sb content exceeds 0.50%, the adhesion of the forsterite film is significantly deteriorated. Therefore, the Sb content is preferably 0.50% or less. The Sb content is more preferably 0.30% or less, and further preferably 0.10% or less.
[0033] Mo: 0 to 0.10% Mo (molybdenum) is an element that has a magnetic property improving effect. Therefore, it may be contained. When Mo is contained, it is preferable that the Mo content is 0.01% or more in order to effectively exhibit the magnetic property improving effect. The Mo content is more preferably 0.02% or more, and further preferably 0.03% or more. On the other hand, if the Mo content exceeds 0.10%, the cold rolling property deteriorates and may lead to fracture. Therefore, the Mo content is preferably 0.10% or less. The Mo content is more preferably 0.08% or less, and further preferably 0.05% or less.
[0034] As described above, the chemical composition of the base steel sheet of the grain-oriented electrical steel sheet in this embodiment may, for example, contain the above-mentioned C, Si, Mn, N, sol.Al, and S with the balance being Fe and impurities, or may contain the elements C, Si, Mn, N, sol.Al, and S, and further contain one or more of P, Cr, Sn, Cu, Se, Sb, Mo, W, Nb, Ti, Ni, Bi, Co, and V with the balance being Fe and impurities. The total content of the elements W to V may be 0.05% or less.
[0035] The Si content in the chemical composition of the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment is determined by the method (silicon quantification method) specified in JIS G 1212 (1997). Specifically, when the above-mentioned cutting chips are dissolved in acid, silicon oxide is precipitated, and this precipitate (silicon oxide) is filtered out with filter paper and the mass is measured to determine the Si content. The chemical composition of the other base steel plate may be determined by a known compositional analysis method. Specifically, a drill is used to generate chips from the base steel plate, the chips are collected, and the collected chips are dissolved in acid to obtain a solution. ICP-AES is performed on the solution to perform elemental analysis of the chemical composition. However, elements that are difficult to measure by ICP-AES, such as the C content and S content, are determined by the well-known high-frequency combustion method (combustion-infrared absorption method). Specifically, the above-mentioned solution may be burned in an oxygen stream by high-frequency heating, and the generated carbon dioxide and sulfur dioxide may be detected to determine the C content and S content. The N content may also be determined by the well-known inert gas fusion-thermal conductivity method. In the grain-oriented electrical steel sheet according to this embodiment, when a forsterite film and / or an insulating film is formed on the surface, these films are removed before measuring the chemical composition of the base steel sheet. The insulating coating can be removed by immersing the grain-oriented electrical steel sheet in an aqueous sodium hydroxide solution containing 30 to 50 mass % NaOH and 50 to 70 mass % H2O at 80 to 90°C for 7 to 10 minutes. The grain-oriented electrical steel sheet from which the insulating coating has been removed is washed with water, and then dried for just under one minute with a hot air blower. The grain-oriented electrical steel sheet after drying (grain-oriented electrical steel sheet without the insulating coating) can be immersed in an aqueous hydrochloric acid solution containing 30-40 mass% HCl at 80-90°C for 1-10 minutes to remove the forsterite coating. After immersion, the base steel sheet is rinsed with water and then dried for just under one minute with a hot air blower, allowing the base steel sheet to be removed from the grain-oriented electrical steel sheet having the forsterite coating and insulating coating.
[0036] (Microstructure) In the grain-oriented electrical steel sheet according to the present embodiment, the grain size in the rolling direction is controlled in the microstructure. Specifically, the area ratio of grains on the surface of the base steel sheet in which the distance between grain boundaries in the rolling direction is 3.0 mm or more and 13.0 mm or less is 70% or more. The crystal grain boundaries that cross the rolling direction change the magnetic domain pattern. In particular, when the distance between the grain boundaries becomes shorter, the 200Hz component of the magnetostriction waveform (sometimes called LvA200Hz) decreases. This is presumably because when the distance between the grain boundaries becomes shorter, the width of the main magnetic domain becomes narrower, which has the effect of suppressing the return domains (lancets) within the grains. If the area ratio of crystal grains having a grain boundary distance (grain boundary interval) of 3.0 mm or more and 13.0 mm or less in the rolling direction is less than 70%, the effect of reducing LvA200Hz is not sufficiently obtained. The area ratio of crystal grains having a grain boundary interval of 3.0 mm or more and 13.0 mm or less is preferably 75% or more, more preferably 80% or more, and even more preferably 90% or more. The upper limit of the area ratio is not limited and may be 100%. The reason why the crystal grains targeted for the area ratio control were crystal grains (regions) with a grain boundary distance of 3.0 mm to 13.0 mm is that in crystal grains with a grain boundary distance of more than 13.0 mm, the domain wall spacing is not sufficiently narrow, and the effect of reducing LvA200Hz is small. On the other hand, from the viewpoint of reducing LvA200Hz, a shorter grain boundary spacing is preferable, but crystal grains with a grain boundary spacing of less than 3.0 mm are concerned as impeding the movement of the domain walls and deteriorating the iron loss characteristics. FIG. 1 shows an example of a magnetic domain pattern observed in the grain-oriented electrical steel sheet according to this embodiment.
[0037] In order to obtain the above-mentioned microstructure, there is a method of irradiating a laser so that the scanning direction of the laser crosses the rolling direction of the base steel sheet, but it is preferable to irradiate so as not to generate fine grains on the irradiation marks. By preventing the generation of fine grains, it is possible to suppress the generation of crystal grains on the surface of the base steel sheet in which the distance between grain boundaries of crystal grains in the rolling direction is less than 3.0 mm. The average grain size in the rolling direction is preferably 3.0 to 20.0 mm. If the average grain size is small, it becomes difficult to achieve an area ratio of 70% or more of crystal grains with a grain boundary distance (grain boundary spacing) of 3.0 mm or more and 13.0 mm or less in the rolling direction, and there is a concern that the iron loss characteristics will deteriorate due to the impeded movement of the domain walls. On the other hand, if the average grain size exceeds 20.0 mm, it becomes difficult to achieve an area ratio of 70% or more of crystal grains with a grain boundary distance of 3.0 mm or more and 13.0 mm or less, and there is a concern that noise will increase.
[0038] The area ratio of crystal grains in which the distance between grain boundaries in the rolling direction is 3.0 mm or more and 13.0 mm or less can be determined by the following method. First, the distance between grain boundaries in the rolling direction is measured by observing the magnetic domains on the surface of the grain-oriented electrical steel sheet using an element for observing magnetic domains. Specifically, the surface of the grain-oriented electrical steel sheet is observed using a reflected electron microscope or an MO sensor that uses the Faraday effect to obtain images, and the grain boundaries are identified from the images based on the direction, spacing, and discontinuity of the magnetic domain walls, and the distance between those grain boundaries in the rolling direction is measured. The area ratio of crystal grains with a predetermined grain boundary spacing is determined by observing an area of 100 mm in the width direction of the surface and 500 mm in the rolling direction, and dividing the area of crystal grains in this observation area with a grain boundary distance in the rolling direction of 3.0 mm to 13.0 mm by the area of the measurement area (x 100 when expressing as a percentage). In this case, a scale along the rolling direction may be used to identify crystal grains that fall outside the range of 3.0 mm to 13.0 mm, measure their areas, and subtract them from the area of the measurement area to measure the area of the target crystal grains (crystal grains with a grain boundary distance in the rolling direction of 3.0 mm to 13.0 mm). In addition, when making the above measurements, the average grain size in the rolling direction can also be measured by drawing a 500 mm straight line from one end of the observation range to the other end in the rolling direction and dividing the length of this line by the number of grain boundaries that intersect with it. The area ratio is measured on the surface of the base steel sheet. According to the above method, the measurement can be performed even if a forsterite film and an insulating film are formed on the base steel sheet, so that it is not necessary to remove the forsterite film and the insulating film when performing the measurement, but they may be removed before the measurement.
[0039] In the grain-oriented electrical steel sheet according to this embodiment, as shown in Fig. 2, short, rectangular closure domains (lancets) 100 are present within the main magnetic domains in the magnetic domains observed on the surface of the base steel sheet. In the grain-oriented electrical steel sheet according to this embodiment, it is preferable that the area ratio of these closure domains (lancets) 100 is 10% or less of the total. If the area ratio of the closure domains 100 exceeds 10%, it becomes difficult to obtain the specified magnetic flux density and iron loss. There is no lower limit to the area ratio, and it may be 0%. In addition, in the grain-oriented electrical steel sheet according to this embodiment, the width of the main magnetic domains observed on the surface and seen to be separated into stripes is preferably set to 1.2 mm or less. If the width exceeds this, lancets 100 are likely to occur, making it difficult to obtain the desired magnetic flux density and iron loss. More preferably, the width of the main magnetic domains is 1.0 mm or less, and even more preferably 0.9 mm or less. The width of the main magnetic domains is affected by the average grain size in the rolling direction, as well as the magnitude of distortion caused by differences in laser irradiation conditions, curvature in the coil state, and the like.
[0040] The area ratio of the closure domains and the width of the main domains are measured on the surface of the base steel sheet in an area of 100 mm in the width direction x 500 mm in the rolling direction using a measuring device such as a CMOS-MagView that utilizes the magneto-optical effect. This method makes it possible to observe magnetic domains even in coated electromagnetic steel sheets. After this, the area of the steel sheet surface of the lancet is measured based on the obtained image, and its presence ratio to the whole is evaluated and the width of the main domain is measured. However, the observation is performed in a demagnetized state.
[0041] (Magnetic properties) The grain-oriented electrical steel sheet according to this embodiment has excellent magnetic properties because its magnetic domains are controlled by laser irradiation. Specifically, when the thickness of the base steel sheet is t in mm, the iron loss W17 / 50 at a frequency of 50 Hz and a maximum magnetic flux density of 1.7 T is 13.1×t in W / kg. 2 -4.3×t+1.2 or less. B8 is less than 1.88T or W17 / 50 is 13.1×t2 If it exceeds -4.3×t+1.2 W / kg, it cannot be said that the magnetic properties are sufficient. Although a high B8 is preferable, if it is assumed that the area of the crystal grains is increased as described above, the practical upper limit is about 1.95T, so B8 may be set to 1.95T or less. In addition, the plate thickness t is the nominal thickness, and if t = 0.23 mm, W17 / 50 is 0.90 W / kg or less. B8 and W17 / 50 are achieved by controlling the manufacturing process, including laser irradiation, to control fine regions such as texture and magnetic domains, but there are multiple factors that change the magnetic properties and they are not easy to measure. Therefore, the grain-oriented electrical steel sheet according to this embodiment is specified by the values of B8 and W17 / 50. As magnetic properties, B8 is preferably 1.92 T or more. As for iron loss, it is preferable that the plate thickness (t) is in the range of 0.18 to 0.23 mm and W17 / 50 is 0.74 W / kg or less.
[0042] B8 and W17 / 50 are measured using test pieces cut from grain-oriented electrical steel sheets to a size of 100 mm in the width direction and 500 mm in the rolling direction, using the Single Sheet Tester (SST) method in accordance with JIS C 2556:2015.
[0043] (Noise characteristics) The grain-oriented electrical steel sheet according to the present embodiment has a LvA200Hz, which is the 200Hz component of the magnetostrictive waveform, of 60 to 78dBA. This allows the noise of the transformer to be reduced when used as a material for the transformer. If the LvA200Hz exceeds 78dB, the noise reduction effect is small. On the other hand, when ensuring predetermined magnetic properties, it is not easy to make the LvA200Hz less than 60dBA, so the LvA200Hz is set to 60dBA or more.
[0044] LvA200Hz is determined by measuring the expansion and contraction of the steel plate using a laser Doppler vibration measuring device in accordance with IEC standard IEC 606404-17 ED1. During the measurement, the steel plate is stretched and contracted by applying an external 50Hz magnetic field. The expansion and contraction of length over time is obtained as a magnetostriction waveform, which is then frequency-analyzed and separated into 100Hz and 200Hz components for evaluation.
[0045] As a result of magnetic domain control, the grain-oriented electrical steel sheet according to this embodiment has the above-mentioned B8 and W17 / 50, and LvA200Hz is 60 to 78dBA, that is, the grain-oriented electrical steel sheet according to this embodiment is a magnetic domain controlled material. Although the method of magnetic domain control is not limited, it is preferable to perform magnetic domain control by laser irradiation under the conditions described below. In this case, a plurality of linear strains extending in a direction intersecting the rolling direction are formed on the surface of the base steel sheet, and the interval between the plurality of linear strains in the rolling direction is 3 to 10 mm. Therefore, the interval between the plurality of linear strains in the rolling direction is preferably 3 to 10 mm. The interval between linear distortions in the rolling direction is the distance in the rolling direction from the center of a linear distortion in the width direction to the center of an adjacent linear distortion in the width direction. In addition, the linear distortion preferably has a width of 250 μm or less in the rolling direction in terms of contributing to improvement of iron loss characteristics. The linear distortion includes a straight line, which is a continuous line, and a dotted line, which is an intermittent line.
[0046] The location of linear strain can be analyzed using residual strain measurement technology using X-ray diffraction (e.g., K. Iwata, et.al, J. Appl. Phys. 117.17A910 (2015)). In addition, if energy beam irradiation marks can be confirmed on the steel sheet surface, the irradiation marks can be judged as strain as they are. Alternatively, a certain distance L of at least L>5 mm may be set in the rolling direction for the observed linear distortion, the number n of distortions present there may be counted, and L / n may be taken as the spacing of the linear distortions in the rolling direction. The width of the linear distortion in the rolling direction may be taken as the average value of the widths of the n measured linear distortions.
[0047] (Thickness) The thickness of the base steel sheet of the grain-oriented electrical steel sheet according to this embodiment is not limited, but when considering application to the iron core of a transformer, which requires low noise as well as low iron loss, it is preferably 0.17 to 0.30 mm. The thinner the plate thickness, the more effective it is in reducing eddy current loss, and the better the iron loss, so the upper limit of the plate thickness of the base steel plate is preferably 0.30 mm. On the other hand, special equipment is required to manufacture a base steel plate with a thickness of less than 0.17 mm, which is undesirable from the viewpoint of production, such as increasing manufacturing costs. Therefore, the industrially preferable lower limit of the plate thickness is 0.17 mm. Preferably, it is 0.18 to 0.23 mm.
[0048] <Forsterite film> In the grain-oriented electrical steel sheet according to the present embodiment, a forsterite film (sometimes called a glass film) is formed on the surface of the base steel sheet. The forsterite film may be a known film. In general, it is an inorganic film mainly composed of magnesium silicate. The forsterite film is formed during the final annealing by the reaction of the annealing separator containing magnesia (MgO) applied to the surface of the base steel sheet with the components of the surface of the base steel sheet, and has a composition derived from the components of the annealing separator and the base steel sheet, and is composed of a structure containing the Mg2SiO4 phase, which is the main phase (50 area % or more), and the MgAl2O4 phase. In addition to these phases, precipitates of about 1% or less may be included.
[0049] <Insulating film> In the grain-oriented electrical steel sheet according to the present embodiment, an insulating film (tension-applying insulating film) is formed on the surface of the forsterite film. The insulating film may be any known film used in the art. The insulating coating imparts electrical insulation to the grain-oriented electrical steel sheet, thereby reducing eddy current loss and improving the iron loss characteristics of the grain-oriented electrical steel sheet (reducing iron loss). In addition to the above-mentioned electrical insulation, the insulating coating also provides various other properties such as corrosion resistance, heat resistance, and slipperiness. Furthermore, the insulating coating has the function of applying tension to the grain-oriented electrical steel sheet. By applying tension to the grain-oriented electrical steel sheet and facilitating domain wall movement in the grain-oriented electrical steel sheet, it is possible to reduce the iron loss of the grain-oriented electrical steel sheet (improve the iron loss characteristics). The insulating coating is formed, for example, by applying a coating liquid mainly composed of metal phosphate and silica to the surface of the forsterite coating and baking it.
[0050] <Manufacturing method> The grain-oriented electrical steel sheet according to this embodiment can be manufactured by a manufacturing method including the following steps. (i) A hot rolling process in which a steel slab having a specified chemical composition is hot rolled to obtain a hot rolled sheet (hot rolled steel sheet). (ii) A cold rolling step of cold rolling the hot rolled sheet to obtain a cold rolled sheet (cold rolled steel sheet) (iii) a decarburization annealing step of subjecting the cold-rolled sheet to decarburization annealing (iv) A finish annealing process in which an annealing separator containing MgO is applied to the cold rolled sheet after the decarburization annealing process, the cold rolled sheet is wound into a coil, and finish annealed. (v) an insulating film forming step of forming an insulating film on the surface of the cold-rolled sheet after the final annealing to obtain a grain-oriented electrical steel sheet; (vi) a laser irradiation step of irradiating the grain-oriented electrical steel sheet having the insulating coating with a laser; The method for producing the grain-oriented electrical steel sheet according to the present embodiment may further include the following steps. (I) a hot-rolled sheet annealing step of annealing the hot-rolled sheet (II) A nitriding process for increasing the nitrogen content of the cold-rolled sheet The manufacturing method of the grain-oriented electrical steel sheet according to the present embodiment is characterized by the above-mentioned (iv) finish annealing step and (vi) laser irradiation step. Preferred conditions for these steps are described below. For the other steps, known manufacturing conditions for grain-oriented electrical steel sheets can be applied. Each step will be described below.
[0051] (Hot rolling process) In the hot rolling process, a steel billet such as a slab is heated and then hot rolled to obtain a hot-rolled sheet. The heating temperature of the steel billet is not particularly limited, but is preferably within the range of 1100 to 1450°C. The hot rolling conditions are not particularly limited and may be appropriately set based on the desired properties. The thickness of the hot rolled sheet obtained by hot rolling is preferably within a range of, for example, 2.0 to 3.0 mm. The chemical composition of the steel slab may be set within a preferred range for obtaining the above-mentioned chemical composition of the base steel sheet, taking into consideration the manufacturing processes after the hot rolling process (taking into consideration changes in chemical composition in each process).
[0052] (Hot-rolled sheet annealing process) The hot-rolled sheet annealing process is a process of annealing the hot-rolled sheet manufactured through the hot rolling process. By carrying out such an annealing treatment, recrystallization occurs in the steel sheet structure, making it possible to realize good magnetic properties. Therefore, it may be carried out. When hot-rolled sheet annealing is performed, the hot-rolled sheet produced through the hot rolling process may be annealed according to a known method. The annealing conditions are not particularly limited, but for example, the hot-rolled sheet may be annealed in a temperature range of 900 to 1200°C for 10 seconds to 5 minutes. The means for heating the hot-rolled sheet during annealing is also not particularly limited, and known heating methods can be adopted. Two-stage annealing in which the annealing temperature is changed midway may also be used.
[0053] (Cold rolling process) In the cold rolling process, the hot rolled sheet after the hot rolled sheet annealing process is subjected to cold rolling including multiple passes to obtain a cold rolled sheet. The cold rolling may be a single pass (a series of passes without intermediate annealing), or may be multiple passes of cold rolling with intermediate annealing by interrupting the cold rolling and performing at least one or two or more intermediate annealing passes before the final pass of the cold rolling process. When intermediate annealing is performed, it is preferable to hold the steel sheet at a temperature of 1000 to 1200° C. for 5 to 180 seconds. The annealing atmosphere is not particularly limited. In consideration of the manufacturing cost, it is preferable to perform intermediate annealing three times or less. In the cold rolling step, the hot rolled sheet is cold rolled according to a known method to obtain a cold rolled sheet. For example, the final rolling reduction can be in the range of 80 to 95%. By setting the final rolling reduction to 80 to 95%, the {110} <001> It is possible to obtain Goss nuclei with a high degree of orientation in the rolling direction, and to suppress the instability of secondary recrystallization. The final rolling reduction is the cumulative rolling reduction of cold rolling, and in the case where intermediate annealing is performed, it is the cumulative rolling reduction of cold rolling after final intermediate annealing. Furthermore, before the cold rolling step, the surface of the hot-rolled sheet may be subjected to pickling under known conditions.
[0054] (Decarburization annealing process) In the decarburization annealing process, the cold-rolled sheet is subjected to decarburization annealing. In decarburization annealing, the cold-rolled sheet is primarily recrystallized and C, which has a negative effect on magnetic properties, is removed from the steel sheet. In addition, the decarburization annealing process increases the number of Goss nuclei in order to refine the secondary recrystallized grains obtained during the finish annealing process described below. Considering that the grain boundaries themselves function as magnetic poles (sites where leakage magnetic flux is generated), the refinement of the secondary recrystallized grains increases the magnetostatic energy of the entire system. In other words, the driving force for magnetic domain refinement is increased. The decarburization annealing conditions may be within the known range, and examples of the conditions include holding in a wet hydrogen and nitrogen atmosphere at an annealing temperature of 750 to 900°C for 10 to 600 seconds. From the viewpoint of controlling the average grain size while taking into account the balance between iron loss and noise, the decarburization annealing temperature is optimal at about 835 to 845°C.
[0055] (Nitriding process) The nitriding process increases the nitrogen content of the steel sheet. The nitriding process may be performed at one or more of the following times: during the decarburization annealing process, between the decarburization annealing process and the finish annealing process, or during the temperature rise process in the finish annealing process until the start of secondary recrystallization. Examples of methods for increasing the nitrogen content of a steel sheet include a method in which the steel sheet is annealed in an atmosphere containing a nitriding gas to control the nitrogen content of the steel sheet, and a method in which a nitriding powder such as MnN is added to an annealing separator during the temperature rise process of the finish annealing step.
[0056] (finish annealing process) In the final annealing process, a specified annealing separator is applied to one or both sides of the cold-rolled sheet obtained in the decarburization annealing process or which has been further subjected to a nitriding treatment, and then the sheet is wound into a coil and subjected to final annealing. In the manufacture of the grain-oriented electrical steel sheet according to this embodiment, a certain degree of curvature is given to the steel sheet (steel strip) when it is wound into a coil, thereby controlling the distance between grain boundaries in the rolling direction and increasing the area ratio of crystal grains with grain boundary distances of 3.0 to 13.0 mm. There are two ways to give curvature: (a) When winding, spacers are placed between the steel sheets. (b) The amount of annealing separator applied is periodically changed. Below, (a) and (b) will be explained. Even without carrying out steps (a) and (b), a curvature is imparted to the steel sheet when it is formed into a coil. In addition, a larger curvature is imparted to the inside of the coil compared to the outside. However, in the usual winding process, it is not possible to impart a sufficient curvature to the steel sheet in order to obtain the grain-oriented electrical steel sheet according to the present embodiment, even on the inside of the coil, which has a relatively large curvature.
[0057] (a) Place a spacer between the steel plates In this method, as shown in Figure 3, when a steel sheet 1 is wound into a coil, ceramic round bars are periodically inserted as spacers 2 perpendicular to the winding direction to periodically change the curvature of the steel sheet. The steel sheet is given a curvature by meandering so that the front side, back side, front side, back side, etc. come into contact with adjacent spacers 2 in the rolling direction of the steel sheet. If the curvature is small, the area ratio of crystal grains with a grain boundary distance of 3.0 to 13.0 mm cannot be increased sufficiently. On the other hand, if the curvature is too large, a preferable crystal orientation cannot be obtained, and the magnetic properties deteriorate. To obtain a predetermined curvature, the diameter (φ) of the spacer 2 (ceramic round bar) is set to 3 to 20 mm, and the interval (L1 in FIG. 3) between the spacers 2 in the rolling direction of the steel sheet 1 is set to 15 to 100 mm.
[0058] (b) The amount of annealing separator applied is periodically changed. In this method, as shown in FIG. 4, the amount (thickness) of the annealing separator 3 applied is changed so that the steel sheet becomes wavy along the rolling direction. In order to impart a constant curvature, annealing separator 3 is applied (positioned) so that the wave height (h in FIG. 4) changes by 3 to 20 mm in a period (L2 in FIG. 4) of 15 to 100 mm in the rolling direction of steel sheet 1.
[0059] Annealing separators are applied to cold-rolled steel sheets to prevent seizure between the inside and outside of the coil turns and to form a forsterite film. In the method for producing grain-oriented electrical steel sheet according to this embodiment, an annealing separator containing MgO as the main component (e.g., 80% by mass or more) is used as the applied annealing separator. By using an annealing separator containing MgO as the main component, a forsterite film can be formed on the surface of the base steel sheet. If MgO is not the main component, a primary film (forsterite film) is not formed. This is because the forsterite film is a Mg2SiO4 or MgAl2O4 compound, and there is a shortage of Mg required for the formation reaction. The annealing separator may further contain TiO2. By containing TiO2, it is possible to obtain an effect of suppressing defective formation of the glass film. The content of TiO2 is, for example, 0 to 10 mass%. The annealing separator can be mixed with water to form a slurry, which can then be applied to the steel sheet.
[0060] After being wound into a coil, the wire is subjected to finish annealing, for example by heating the wire to 1150 to 1250° C. in an atmospheric gas containing hydrogen and nitrogen, and holding the wire in that temperature range for 10 to 60 hours.
[0061] (Insulation film formation process) In the insulating film forming process, an insulating film (tensioned insulating film) is formed on one or both sides of the cold-rolled sheet after the finish annealing. The conditions for forming the insulating film are not particularly limited, and a known insulating film treatment liquid may be used, and the treatment liquid may be applied and dried by a known method. By forming an insulating film on the steel sheet surface, it is possible to further improve the magnetic properties of the grain-oriented electrical steel sheet. The surface of the steel sheet on which the insulating coating is formed may be a surface that has been subjected to any pretreatment, such as a degreasing treatment with an alkali or an acid pickling treatment with hydrochloric acid, sulfuric acid, phosphoric acid or the like, before the treatment liquid is applied, or the surface may be as it is after finish annealing without being subjected to such pretreatment. The insulating film formed on the surface of the steel sheet is not particularly limited as long as it is used as an insulating film for oriented electrical steel sheets, and a known insulating film can be used. Examples of such insulating films include films mainly composed of phosphate and colloidal silica. Examples of composite insulating films include inorganic substances and organic substances. Here, the composite insulating film is an insulating film mainly composed of at least one of inorganic substances such as metal chromate salts, metal phosphate salts, colloidal silica, Zr compounds, and Ti compounds, in which fine organic resin particles are dispersed. In particular, from the viewpoint of reducing the environmental load during production, which has become increasingly necessary in recent years, insulating films using metal phosphate salts, Zr or Ti coupling agents, or carbonates or ammonium salts thereof as starting materials may be used.
[0062] (Laser irradiation process) In the laser irradiation process, a laser beam is irradiated onto the grain-oriented electrical steel sheet on which the insulating film has been formed, and magnetic domain control is performed, thereby improving the magnetic properties. The laser irradiation conditions are, for example, a laser input energy Ua of 1.0 to 4.0 mJ / mm 2 The laser power density Ip is 500 to 4000 W / mm 2 The laser beam is irradiated so as to extend in a direction intersecting the rolling direction (for example, a direction at an angle of 60 to 120° to the rolling direction) (preferably from one end of the steel plate in the width direction to the other end), and is irradiated multiple times (preferably over the entire length of the steel plate) so that the interval PL in the rolling direction is 3 to 10 mm and the respective irradiation directions are approximately parallel. Ua is 1.0mJ / mm 2 Less than or equal to 500W / mm 2 If the magnetic field is less than 4.0 mJ / mm, sufficient magnetic domain refinement effect cannot be obtained. 2 or Ip is over 4000W / mm 2 Above this level, noise characteristics deteriorate. This is thought to be due to the large number of closure domains. Ip is preferably 2000W / mm 2 The following is the result. EXAMPLES
[0063] The grain-oriented electrical steel sheet according to the present invention will be specifically described below with reference to examples. The examples shown below are merely examples, and the grain-oriented electrical steel sheet according to the present invention is not limited to the following examples.
[0064] <Example 1> A steel slab containing 0.055% C, 0.86-3.15% Si, 0.14% Mn, 0.007% S, 0.027% sol.Al, 0.12% Cr, 0.0075% N, with the balance being Fe and impurities, was heated to 1150°C and then hot-rolled to form a hot-rolled sheet having a thickness of 2.3 mm. The hot-rolled sheet was then annealed by heating to 1120°C and holding for 180 seconds, then lowering to 900°C and holding at that temperature for 120 seconds, followed by quenching using boiling water at 100°C. Thereafter, the steel sheet was pickled and then cold rolled to obtain a cold rolled sheet having a thickness of 0.23 mm. Next, this cold-rolled sheet (steel sheet) was subjected to decarburization annealing by heating in a wet hydrogen and nitrogen atmosphere to the temperature shown in Table 1 and holding for 150 seconds. After decarburization annealing, the cold-rolled sheet was heated to 750°C in an atmosphere consisting of 25% N2, 75% H2 with added NH3, and held at that temperature for 30 seconds, thereby performing a nitriding treatment to increase the N content of the steel sheet to 180 ppm. After the nitriding treatment, a known annealing separator containing MgO and TiO2 as main components and Na, B, Cl, etc. was applied, and final annealing was performed by holding at 1200°C for 20 hours. At this time, spacers were placed at regular intervals between the steel sheets to make the steel sheets wavy, and the steel sheets were wound into a coil and then final annealing was performed. The diameter and spacing of the spacers (ceramic rods) were as shown in Table 1. After final annealing, a forsterite film was formed on the surface. After finish annealing, a coating liquid containing chromic anhydride and aluminum phosphate as main components was applied to the surface of this steel sheet (a steel sheet having a forsterite film formed on the surface of the base steel sheet), and bake annealing was performed to form an insulating film. After that, the surface of the steel sheet on which the insulating film was formed was irradiated with a laser beam to perform magnetic domain refinement (magnetic domain control). At that time, the laser input energy and laser power density were as shown in Table 1. The scanning direction of the laser beam (extension direction of the irradiation marks) was set to a direction of 90° to the rolling direction, and the interval in the rolling direction between adjacent irradiation positions of the laser beam (the interval in the rolling direction between multiple linear distortions) was set to 4 mm.
[0065] The chemical composition, the ratio of crystal grains with a grain boundary distance of 3.0 to 13.0 mm in the rolling direction, the area ratio of lancets, the width of the striped main magnetic domains, the magnetic properties (B8 and W17 / 50), and the value of LvA200Hz were determined for the steel sheet (grain-oriented electrical steel sheet) after magnetic domain control using the above-mentioned method. The magnetic domains were observed in a demagnetized state. In addition, the average grain size in the rolling direction on the surface, and the width of the linear distortions formed at 4 mm intervals in the rolling direction over the entire area of the steel sheet in the rolling direction (average of multiple linear distortions) were also determined. The results are shown in Table 1. 。
[0066] [Table 1]
[0067] As can be seen from Table 1, in the example of the present invention, the area ratio of crystal grains on the surface of the base steel sheet in which the distance between the grain boundaries of crystal grains in the rolling direction is 3.0 mm or more and 13.0 mm or less is 70% or more, B8, which is the magnetic flux density generated by a magnetizing force of 800 A / m, is 1.88 T or more, and W17 / 50, in units of W / kg, is 13.1 x t 2 The value was -4.3×t+1.2 or less, and LvA200Hz was 60 to 78 dBA. No fine particles were observed on the irradiation marks. In contrast to this, in the comparative examples, one or more of the above points are outside the range of the present invention, and iron loss and noise cannot be sufficiently reduced at the same time. For example, in No. 12, the decarburization annealing temperature is slightly low, and Ip is 1100 W / mm 2 Despite this, the average grain size was small at 2.8 mm, and the area ratio of grains with a grain boundary distance of 3.0 mm to 13.0 mm in the rolling direction was small. In addition, B8 was low, iron loss was high, and LvA200Hz was high. In No. 13, the decarburization annealing temperature was slightly high, the average grain size was large at 20.2 mm, and the area ratio of crystal grains with a grain boundary distance of 3.0 mm to 13.0 mm in the rolling direction was small. As a result, LvA200Hz was high. In No. 16, the laser input energy Ua was 4.1 mJ / mm 2 was relatively high, and as a result, LvA200Hz was high. In No. 17, the laser input energy Ua was 4.4 mJ / mm 2 was relatively high, and as a result, LvA200Hz was high. In No. 19, the spacer diameter and spacer interval were not within the preferred range, so the average grain size was large at 21.2 mm, and the area ratio of crystal grains with a grain boundary distance of 3.0 mm to 13.0 mm in the rolling direction was small. As a result, LvA200Hz was high. In No. 20, the laser power density Ip is 200 W / m 2 The surface area ratio of crystal grains with a grain boundary distance of 3.0 mm to 13.0 mm in the rolling direction was small. As a result, the iron loss was high.
[0068] <Example 2> A steel slab containing 0.070% C, 3.08-3.24% Si, 0.09% Mn, 0.006% S, 0.026% sol.Al, 0.11% Cr, 0.0076% N, with the balance being Fe and impurities, was heated to 1140°C and hot rolled to form a hot-rolled sheet having a thickness of 2.4 mm. The hot-rolled sheet was then annealed by heating to 1120°C and holding for 180 seconds, then lowering to 900°C and holding at that temperature for 120 seconds, followed by quenching using boiling water at 100°C. Thereafter, the steel sheet was pickled and then cold rolled to obtain a cold rolled sheet having a thickness of 0.23 mm. Next, this cold-rolled sheet (steel sheet) was subjected to decarburization annealing by heating in a wet hydrogen and nitrogen atmosphere to the temperature shown in Table 2 and holding for 150 seconds. After the decarburization annealing, a known annealing separator containing MgO and TiO2 as main components and Na, B, Cl, etc. was applied, and final annealing was performed by holding at 1200°C for 20 hours. At this time, as shown in Figure 4, the annealing separator was distributed between the steel sheets so that the thickness changed at regular intervals, and the steel sheets were wound into a coil and final annealing was performed. The annealing separator was applied to different thicknesses so that the steel sheets were wavy with wave heights changing with the wave period (rolling direction) shown in Table 2. After final annealing, a forsterite film was formed on the surface. After final annealing, a coating liquid containing chromic anhydride and aluminum phosphate as its main components was applied to the surface of this steel sheet (a steel sheet with a forsterite film formed on the surface of the base steel sheet), and then baked annealing was performed to form an insulating film. After that, the surface of the steel sheet on which the insulating film was formed was irradiated with a laser beam to perform magnetic domain refinement (magnetic domain control). At that time, the laser input energy and laser power density were as shown in Table 2. The scanning direction of the laser beam (extension direction of the irradiation mark) was set to a direction of 90° to the rolling direction, and the interval in the rolling direction between adjacent laser beam irradiation positions was set to 4 mm.
[0069] [Table 2]
[0070] The chemical composition, the percentage of crystal grains with a grain boundary distance of 3.0 to 13.0 mm in the rolling direction, the area ratio of lancets, the width of the striped main magnetic domains, the magnetic properties (B8 and W17 / 50), and the value of LvA200Hz were determined for the steel sheet (grain-oriented electrical steel sheet) after magnetic domain control using the above-mentioned method. The magnetic domains were observed in a demagnetized state. The average grain size in the rolling direction on the surface and the width of multiple linear distortions formed at intervals of 4 mm in the rolling direction (average of multiple linear distortions) were also determined. The results are shown in Table 2. 。
[0071] As can be seen from Table 2, in the example of the present invention, the area ratio of crystal grains on the surface of the base steel sheet in which the distance between the grain boundaries of crystal grains in the rolling direction is 3.0 mm or more and 13.0 mm or less is 70% or more, B8, which is the magnetic flux density generated by a magnetizing force of 800 A / m, is 1.88 T or more, and W17 / 50, in units of W / kg, is 13.1 x t 2 -4.3×t+1.2 or less, and LvA200Hz is 60 to 78dBA. Here, the laser was irradiated transversely to the rolling direction of the steel plate, but this did not result in fine grains on the irradiation marks. In contrast to this, in the comparative examples, one or more of the above points are outside the range of the present invention, and iron loss and noise cannot be sufficiently reduced at the same time. In No. 24, the decarburization annealing temperature was somewhat low, and even though the laser power density and other factors were within the preferred range, the area ratio of crystal grains with a grain boundary distance of 3.0 mm to 13.0 mm in the rolling direction was small. In addition, B8 was low, LvA200Hz was high, and W17 / 50 was high. In No. 25, the decarburization annealing temperature was slightly high, the average grain size was large, and the area ratio of crystal grains with a grain boundary distance of 3.0 to 13.0 mm in the rolling direction was low. As a result, LvA200Hz was high. Also, W17 / 50 was high. In No. 26 and No. 27, the laser input energy was large, and as a result, LvA200Hz was high. Also, W17 / 50 was high. In No. 28, the wave period was large, so the average grain size was large and the area ratio of crystal grains with a grain boundary distance of 3.0 mm to 13.0 mm in the rolling direction was small. As a result, LvA200Hz was high. [Explanation of symbols]
[0072] 100 lancets (reflux domains) 1 steel plate 2 Spacers 3 Annealing separator L1 Spacer spacing L2 period h Wave height
Claims
1. A base steel plate; A forsterite film formed on the surface of the base steel sheet; an insulating coating formed on a surface of the forsterite coating; Equipped with The chemical composition of the base steel sheet contains, in mass%, Si: 0.80 to 7.00%, The area ratio of crystal grains on the surface of the base steel sheet, in which the distance between grain boundaries of crystal grains in the rolling direction is 3.0 mm or more and 13.0 mm or less, is 70% or more; B8, which is the magnetic flux density generated by a magnetizing force of 800 A / m, is 1.88 T or more, When the plate thickness of the base steel plate is t in mm, the iron loss W17 / 50 when the frequency is 50 Hz and the maximum magnetic flux density is 1.7 T is 13.1 x t in W / kg. 2 -4.3 × t + 1.2 or less, LvA200Hz, which is the 200Hz component of the magnetostrictive waveform, is 60 to 78dBA, A plurality of linear strains extending in a direction intersecting the rolling direction are formed on the surface of the base steel sheet, and the intervals of the plurality of linear strains in the rolling direction are 3 to 10 mm. The grain-oriented electrical steel sheet is characterized in that
2. In the base steel sheet, the area ratio of the rectangular closure domains observed on the surface is 10% or less, and the width of the stripe-shaped main domains is 1.2 mm or less. The grain-oriented electrical steel sheet according to claim 1 .
3. When the magnetic flux density is 1.92 T or more and the plate thickness is 0.18 to 0.23 mm, the W17 / 50 is 0.74 W / kg or less; The grain-oriented electrical steel sheet according to claim 1 or 2.
Citation Information
Patent Citations
Low-noise feature oriented silicon steel and manufacturing method thereof
CN105220071A
High-magnetic-induction oriented silicon steel with low-noise characteristic and production method
CN112159935A
Valve-gap adjusting method for internal-combustion engine
JP1983096112A
Grain oriented electrical steel sheet
JP2020169374A
Grain-oriented electromagnetic steel sheet
JP2021123755A
